Global constraints from RHIC and LHC on transport properties of QCD fluids in CUJET/CIBJET framework *Supported by the National Science Foundation (PHY-1352368), IOPP of CCNU Wuhan China, the computations in this study were performed on IU's Big Red II clusters, supported in part by the Lilly Endowment, Inc., through its support for the Indiana University Pervasive Technology Institute, and in part by the Indiana METACyt Initiative. The Indiana METACyt Initiative at IU was also supported in part by the Lilly Endowment, Inc. (April 2019) - Shi 施, Shuzhe 舒哲; Liao 廖, Jinfeng 劲峰; Gyulassy, Miklos
Abstract: We report results of a comprehensive global analysis of nuclear collision data from RHIC (0.2 ATeV), LHC1 (2.76 ATeV), and recent LHC2 (5.02 ATeV) energies using the updated CUJET framework. The framework consistently combines viscous hydrodynamic fields predicted by VISHNU2+1 (validated with soft GeV bulk observables) and the DGLV theory of jet elastic and inelastic energy loss generalized to QGP fluids with an sQGMP color structure, including effective semi-QGP color electric quark and gluon as well as emergent color magnetic monopole degrees of freedom constrained by lattice QCD data. We vary the two control parameters of the model (the maximum value of the running QCD coupling, , and the ratio of color magnetic to electric screening scales) and calculate the global compared with available jet fragment observables ( ). A global minimum is found with and . Using CIBJET, the event-by-event (ebe) generalization of the CUJET framework, we show that ebe fluctuations in the initial conditions do not significantly alter our conclusions (except for ). An important theoretical advantage of the CUJET and CIBJET frameworks is not only its global consistency with jet fragment observables at RHIC and LHC and with non-perturbative lattice QCD data, but also its internal consistency of the constrained jet transport coefficient, , with the near-perfect fluid viscosity to entropy ratio ( ) property of QCD fluids near needed to account for the low GeV flow observables. Predictions for future tests at LHC with 5.44 ATeV Xe + Xe and 5.02 ATeV Pb + Pb are also presented.